Attitudes Toward Mathematics and Their Association With Academic Achievement Among Distance Education Students - Araya Román, Daniela (2026)
The aim of this study was to examine the association between the dimensions of attitudes toward mathematics —specifically mathematics anxiety, enjoyment, perceived usefulness, motivation, and confidence— and the final grade in the course Mathematics for Administrators II, offered during the third academic term of 2024, in a sample of students enrolled in the Business Administration program at the Universidad Estatal a Distancia de Costa Rica. Differences by sex, course repetition status, and scholarship status were also analyzed. A quantitative, non-experimental, cross-sectional, correlational study was conducted using an attitude scale with adequate internal consistency (α = 0.903; ω = 0.904). Given the non-normality of the data, nonparametric tests (Mann–Whitney and Kruskal–Wallis) and multiple linear regression were applied for explanatory purposes. The results showed that students repeating the course obtained lower grades, whereas men reported more favorable attitudes and lower mathematics  anxiety than women. In addition, scholarship status was associated with higher levels of mathematics anxiety. In the regression model, enjoyment, motivation, and confidence were positively and significantly associated with academic achievement, with moderate overall model fit. The findings indicate an association between attitudes toward mathematics and academic achievement, underscoring the importance of the instructional context. Learning environments that strengthen confidence, perceived usefulness, motivation, and enjoyment through interventions aimed at reducing mathematics anxiety are recommended. Longitudinal and multilevel studies are further recommended to deepen causal understanding and disentangle the observed effects.